Maternal and Foetal Outcome in Term Pregnancy with Oligohydramnios (Journal of Armed Forces Medical College, Bangladesh, 2026)
Background: Oligohydramnios is defined where the amniotic fluid index below the 5th centile for gestational age. This can occur 1-5% of all pregnancies, it rises more than 12% in post term pregnancies worldwide. It is associated with adverse perinatal outcome like foetal lung hypoplasia, foetal limb deformities-potters syndrome and preterm delivery, foetal growth restriction and foetal renal congenital anomalies.Objective: To study the outcome of pregnancies with severe oligohydramnios (AFI 2.5 kg, and the mean APGAR score at 5 minutes was 8.2±1.1. The associated IUGR were 38% cases, congenital anomalies were present only in 2% of cases. Forty-seven neonates (47%) required admission to the NICU and no neonatal deaths were reported.Conlcusion: Oligohydramnios is associated with foetal and neonatal death which may related to underlying cause of oligohydramnios or sequelae of reduced amniotic fluid volume or both.JAFMC Bangladesh, Vol 21, No 2 (December) 2025:40-43